2012
DOI: 10.1109/tuffc.2012.2506
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic cardiac ultrasonic stimulation induces a negative chronotropic effect

Abstract: The objective of this study is to investigate cardiac bioeffects resulting from ultrasonic stimulation using a specific set of acoustical parameters. Ten Sprague–Dawley rats were anesthetized and exposed to 1-MHz ultrasound pulses of 3-MPa peak rarefactional pressure and approximately 1% duty factor. The pulse repetition frequency started slightly above the heart rate and was decreased by 1 Hz every 10 s, for a total exposure duration of 30 s. The control group was composed of five rats. Two-way analysis of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 21 publications
2
49
1
Order By: Relevance
“…Because there were no signs of major problems to animals exposed to the pulsed sequence, 11 animals were allowed to recover.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because there were no signs of major problems to animals exposed to the pulsed sequence, 11 animals were allowed to recover.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study 11 demonstrated that transthoracic ultrasound can promote a negative chronotropic effect without impairing cardiac pumping function and/or damaging cardiac tissue. 11 This effect was achieved using a specific sequence of 1-MHz ultrasonic bursts delivered transthoracically to the heart, progressively decreasing the PRF while maintaining the same DF.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therapeutic effects of cardiac ultrasound have been examined through in vitro and in vivo studies [2]–[9]. In vitro cardiac tissue observations in frogs, guinea pigs, rats, dogs, and pigs included defibrillation [3], premature contraction of myocardium [7], [10]–[12], negative chronotropic effect [9], and positive inotropic/lusitropic effect [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic effects of cardiac ultrasound have been examined through in vitro and in vivo studies [2]–[9]. In vitro cardiac tissue observations in frogs, guinea pigs, rats, dogs, and pigs included defibrillation [3], premature contraction of myocardium [7], [10]–[12], negative chronotropic effect [9], and positive inotropic/lusitropic effect [13]. In vivo observations of pulsed ultrasound (US) delivered to the animal heart caused a variety of effects such as intravascular bubbles [4], arrhythmias [5], changes in cardiac rhythm and aortic pressure [6], and cardiac pacing [8].…”
Section: Introductionmentioning
confidence: 99%